Student support as social network: exploring non-traditional student experiences of academic and wellbeing support during the Covid-19 pandemic. Issue 3 (16th April 2022) - Raaper, Rille; Brown, Chris; Llewellyn, Anna
ABSTRACT: The Covid-19 pandemic has caused a global crisis in higher education, affecting all aspects of university work and practices. This article focuses on student experiences, in particular by problematising academic and wellbeing support available to non-traditional students. This article proposes an original approach to student support as comprising social networks that are dynamic, reciprocal and involving a variety of formal/informal actors. We draw on interviews with 10 non-traditional students from a UK university to explore the nature of their student support. Our findings suggest that support networks for non-traditional students tend to exclude formal support services and centre primarily around family (wellbeing support) and fellow students (academic/wellbeing support). While these findings problematise the lack of institutional support in student networks which is likely to further disadvantage these students, it questions the dominant deficit views of non-traditional students. In particular, the interviews highlight the resourcefulness of close interactions and emphasise the importance of approaching student support as a dynamic network of informal and formal actors when responding to crisis situations such as the Covid-19 pandemic.